SISTEM INFORMASI PENGAJUAN KLAIM PESERTA JAMINAN KESEHATAN (JKN) BERBASIS WEB DI RUMAH SAKIT Dr. M.M. DUNDA LIMBOTO - Lasena, Marlin (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2020)
Changes in technology currently affect all aspects including health, to increase effectiveness and efficiency in the service, it is necessary to change to the old system to facilitate the patient and the parties Health service Provider in conducting health service process. Everyone has the right to live prosperous lives, reside, and gain a good and healthy environment and deserve health care